Institutional Interventions to Reduce Risks of Shallot Farmers in Bima Regency - Hardinandar, Fajrin; Hung, Chia-Yu (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  The theory of market institutions emphasizes the Government's role in creating a healthy and competitive market structure, such as through policies that encourage market access diversification for farmers, strengthening farmers' bargaining position, and oversight of monopolistic or oligopolistic practices. However, most of the falling prices faced by shallot farmers in Bima Regency, one of the shallot production centers in West Nusa Tenggara Province, Indonesia, stems from the pull and push forces between supply and demand at the national level. The weak Government intervention in market institutions exacerbates this problem. The laboratory experiment results showed that the probability of market failure risk faced by shallot farmers reaches 86% when no institutional intervention exists. This finding emphasized the urgency of the role of institutional intervention in reducing the risks faced by shallot farmers in Bima Regency. The lessons from this laboratory experiment also emphasized that institutional interventions through Regional-Owned Enterprises (BUMD) and the formation of distributor clusters effectively reduce the risk of market failure farmer face. Meanwhile, the collective community power among farmers can be social capital to support the success of institutional interventions.